Safety and efficacy of matrix-associated autologous chondrocyte implantation with spheroids for patellofemoral or tibiofemoral defects: a 5-year follow-up of a phase 2, dose-confirmation trial - Hoburg, Arnd Thomas; Niemeyer, Philipp; Laute, Volker; Zinser, Wolfgang; John, Thilo; Becher, Christoph; Izadpanah, Kaywan; Diehl, Peter; Kolombe, Thomas; Fay, Jakob; Siebold, Rainer; Fickert, Stefan (Orthopaedic journal of sports medicine, 2022)
Background:Matrix-associated autologous chondrocyte implantation (ACI) is a well-established treatment for cartilage defects. High-level evidence at midterm follow-up is limited, especially for ACI using spheroids (spherical aggregates of ex vivo expanded human autologous chondrocytes and self-synthesized extracellular matrix).Purpose:To assess the safety and efficacy of 3-dimensional matrix-associated ACI using spheroids to treat medium to large cartilage defects on different locations in the knee joint (patella, trochlea, and femoral condyle) at 5-year follow-up.Study Design:Cohort study; Level of evidence, 2.Methods:A total of 75 patients aged 18 to 50 years with medium to large (4-10 cm2), isolated, single cartilage defects, International Cartilage Repair Society grade 3 or 4, were randomized on a single-blind basis to treatment with ACI at 1 of 3 dose levels: 3 to 7, 10 to 30, or 40 to 70 spheroids/cm2 of defect size. Outcomes were assessed via changes from baseline Knee injury and Osteoarthritis Outcome Score (KOOS), International Knee Documentation Committee score, and modified Lysholm assessments at 1- and 5-year follow-up. Structural repair was evaluated using MOCART (magnetic resonance observation of cartilage repair tissue) score. Treatment-related adverse events were assessed up to 5 years for all patients. The overall KOOS at 12 months was assessed for superiority versus baseline in a 1-sample, 2-sided t test.Results:A total of 73 patients were treated: 24 in the low-dose group, 25 in the medium-dose group, and 24 in the high-dose group. The overall KOOS improved from 57.0 ± 15.2 at baseline to 73.4 ± 17.3 at 1-year follow-up (P < .0001) and 76.9 ± 19.3 at 5-year follow-up (P < .0001), independent of the applied dose. The different defect locations (patella, trochlea, and weightbearing part of the femoral condyles; P = .2216) and defect sizes (P = .8706) showed comparable clinical improvement. No differences between the various doses were observed. The overall treatment failure rate until 5 years was 4%. Most treatment-related adverse events occurred within the first 12 months after implantation, with the most frequent adverse reactions being joint effusion (n = 71), arthralgia (n = 14), and joint swelling (n = 9).Conclusion:ACI using spheroids was safe and effective for defect sizes up to 10 cm2 and showed maintenance of efficacy up to 5 years for all 3 doses that were investigated.Registration:NCT01225575 (ClinicalTrials.gov identifier); 2009-016816-20 (EudraCT number).